Polmas Gastronomy: The Transformation of Street Vendors Towards a Participatory Community Security System in Indonesia - Putra, Madiya Mawlana; Simanjuntak, Raja Luat; Bhiswara, Priya Kuntha; Faidzin, Syahrul; Dicky, Febrian (Indonesian National Police Academy, 2025)
As public trust in conventional policing models continues to swirl downward, this study builds on Indonesia's unique street food culture and the establishment of Gastronomy “Polmas” (Police and Community) - a community security framework that activates street food vendors as organic intelligence agents. This study will look at the